AIGC empowers research on the communication path of red culture in six places in Liaoning - Wang, Xu; Zhou, Xu (Transactions on Social Science, Education and Humanities Research, 2024)
As a region rich in red cultural resources, Liaoning’s revolutionary history, heroic deeds and red spirit have profound connotations and important contemporary value. However, traditional communication methods are no longer able to meet the diverse needs of modern society. Technological development and structural innovation in the AIGC field have restructured the current media landscape and communication paths. With the help of AIGC technology, it is particularly important to improve the efficiency and influence of red cultural communication. This article aims to explore how AIGC empowers the communication path of red culture in six places in Liaoning, with a view to giving full play to the significant advantages and potential of AIGC technology in the communication of red culture, improving the accuracy and interactivity of communication, and stimulating the audience’s emotional resonance and cultural identity. , providing strong support for the spread and development of red culture. Keywords: AIGC, six places in Liaoning, red culture, communication path.